THE ANALYSIS OF METAPHORS THAT HAVE LINGUACULTURALOGICAL IMPORTANCE - Ziyatova, Nafosat (Журнал иностранных языков и лингвистики, 2021)
Figurative word-metaphors that are used only by certain nations have their linguaculturalogical importance. Metaphors are normally used to add emotional color to the idea being expressed. This types of metaphors are typical occurrences in the Uzbek liguaculture and they are considered to be national and cultural treasures of the nation. The article analyses and deals with national-cultural aspects of metaphors in the works of O'tkir Hoshimov.